2017
DOI: 10.1080/15459624.2017.1319571
|View full text |Cite
|
Sign up to set email alerts
|

Performance of two respiratory protective devices used by home-attending health care workers (a pilot study)

Abstract: Wearing an N95-certified respirator helps significantly reduce the aerosol inhalation exposure of home-attending health care workers. An SM offers much lower protection. The WPF depends on several factors, including, but not limited to, the health care worker's activity and/or body movements; the WPF varies from one worker to another.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 6 publications
3
9
1
Order By: Relevance
“…As reported by Elmashae and coworkers (Elmashae et al 2017), which tested different filter materials accordingly to identify airborne bacterial cells, our results showed similar detection rates with all tested filter materials. It has to be mentioned, that pore sizes of the different membrane filter discs tested in the bioaerosol chamber were not identical, but a similar size range (Versapor 1.2 µm pore size; Cellulose Nitrate and Polycarbonate 0.8 µm pore sizes).…”
Section: Discussionsupporting
confidence: 88%
“…As reported by Elmashae and coworkers (Elmashae et al 2017), which tested different filter materials accordingly to identify airborne bacterial cells, our results showed similar detection rates with all tested filter materials. It has to be mentioned, that pore sizes of the different membrane filter discs tested in the bioaerosol chamber were not identical, but a similar size range (Versapor 1.2 µm pore size; Cellulose Nitrate and Polycarbonate 0.8 µm pore sizes).…”
Section: Discussionsupporting
confidence: 88%
“…Modelling studies 122 , 123 , 124 and simulated workplace protection studies 125 , 126 , 127 in the USA have shown benefits of various types of respirators and little to no protection from surgical masks. A study in the UK found that surgical masks could reduce inert aerosol exposure by two times, but filtering facepiece respirators reduced the exposure by a factor of 100 or higher.…”
Section: Implications Of Infectious Aerosol Data For Infection Contromentioning
confidence: 99%
“…Laboratory/controlled settings In experimental settings, N95 respirators demonstrate efficient filtration of nanoparticles and bioaerosols. [6][7][8][9] When compared with surgical masks in this setting, N95 respirators provide superior protection against aerosols and viruses similar in size to influenza, especially when combined with eye protection. 6 8 10-12 In one study, layering of up to five surgical masks improved in vivo filtration efficiency, though fit factor scores using this strategy remain markedly inferior to the minimum required for N95 respirators (13.7 vs 100).…”
Section: Medical-grade Facial Protectionmentioning
confidence: 99%